How do ergonomic factors affect students’ online learning in tertiary education? - Walker, Rebecca; Jansz, J.; Bay, J.; Paudel, N.; Swapan, A.; Smith, R. (World Safety Organization, 2018)
Aim: The aim of this research was to identify and evaluate the physical, environmental, organisational, cognitive and social ergonomic factors associated with student learning in online tertiary education. Results : Results of this exploratory descriptive study identified that physical, environmental, cognitive, organisational and social ergonomic factors were all important in facilitating student online learning, but could also hinder learning when any of these 5 ergonomic factors were unsatisfactory. The Tutor was identified as having an important role in students’ online learning. Environmental ergonomic factors were of most concern followed in descending levels of concern by physical, organisational, social and cognitive ergonomic factors. The environmental ergonomic factor of most concern was noise as it distracted students’ concentration, thereby negatively impacting on student satisfaction and learning. Conclusions: It was concluded that students perceived organisational ergonomics to be the most important of all five ergonomic factors for providing an effective online learning environment followed in declining levels of importance by cognitive, physical, environmental and social ergonomic factors. The organisational ergonomic factor considered of most concern was technical issues with inadequate access to the learning platform Blackboard, which interrupts and limits students’ online learning.